Risk Factors for Chronic Pain Syndrome after Gynecological Surgery - M. Z Dugiyeva; S. V. Sviridov; N. I. Sleptsova; K. V. Morozova (Общая реаниматология, 2012)
Objective: to define risk factors for chronic postoperative pain syndrome (CPPS) in gynecological patients. Subjects and methods. The pre- and intraoperative examination data of 339 gynecological patients who had been operated on via only laparotomic approach and received postoperative traditional therapy (without adaptogens and antioxidants) were used to study the risk factors of CPPS. Postoperatively, subjective self-assessment tests were carried out using the visual analogue scale (VAS) and 4-point pain rating scale to measure pain intensity. Results. The material of 339 patients who had undergone gynecological surgery was used to investigate the importance of CPPS risk factors associated with their preoperative features and with the indicators characterizing the performed intervention. The reasons that were of statistically confirmed significance to the risk of CPPS were identified. The findings may be used to individualize a postoperative analgesic therapy regimen and they determine priority measures to prevent CPPS. Conclusion. The reasons associated with a significant increase in the relative risk of CPPS (RR, 1.3 to 2.6; p<0.05) are a more than 2-hour operation, an intraoperative blood loss exceeding 500 ml, third-to-fourth-degree obesity, anemia with a preoperative hemoglobin concentration of < 100 g/l, and preoperative sympatotonia. The factors that are of no statistically confirmed significance to the risk of CPPS (p>0.05; 95% CI for RR and OR) are anemia with a preoperative hemoglobin concentration of 100 to 120 g/l, first-to-second-degree obesity, a less than 2-hour operation, an intraoperative blood loss of less than 500 ml, and preoperative parasympatotonia. Key words: gynecological surgery, chronic postoperative pain syndrome, risk factors.